1984
DOI: 10.1161/01.res.54.5.566
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cerebroventricular infusion of hypertonic sodium chloride in rats reduces hypothalamic sympatho-inhibition and elevates blood pressure.

Abstract: SUMMARY. To determine whether or not salt loading restricted to the brain would elevate blood pressure, chronically implanted osmotic minipumps were used to infuse hypertonic sodium chloride solutions made in artificial cerebrospinal fluid into a jugular vein intravenously or the third cerebral ventricle, intracerebroventricularly, for 11 days in awake rats. During intracerebroventricular infusion of hypertonic sodium chloride, tail-cuff systolic pressures began to rise on day 4 and were significantly elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 29 publications
(28 reference statements)
2
31
0
Order By: Relevance
“…Our results confirm the findings of a few previous studies. Miyajima and Bunag 17 showed that third ventricular infusion of 0.8 M NaCl at the same infusion rate for 11 days elevated blood pressure in rats. Katahira et al 21 also observed that chronic administration of 1.5 M NaCl into the lateral ventricle of rats caused a moderate increase in blood pressure.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our results confirm the findings of a few previous studies. Miyajima and Bunag 17 showed that third ventricular infusion of 0.8 M NaCl at the same infusion rate for 11 days elevated blood pressure in rats. Katahira et al 21 also observed that chronic administration of 1.5 M NaCl into the lateral ventricle of rats caused a moderate increase in blood pressure.…”
Section: Resultsmentioning
confidence: 98%
“…14 -16 Although the central effects of hypertonic NaCI are well documented in acute experiments, there are few chronic studies. Miyajima and Bunag 17 reported that intracerebroventricular infusion of hypertonic NaCI for 11 days caused mild hypertension and reduced depressor response to anterior hypothalamic stimulation in rats. They also observed that impairment of the baroreceptor reflex preceded the rise in blood pressure.…”
mentioning
confidence: 99%
“…12,13 These and other results indicate that dietary NaCl loading increases blood pressure in male SHR by reducing norepinephrine release in AHN, thus removing an important sympatho-inhibitory mechanism that normally modulates arterial pressure. [25][26][27][28][29] Other studies indicate that a high NaCl diet elevates plasma sodium, which in turn activates osmo-receptive neurons in the circumventricular hypothalamic nuclei. 30 -32 The activation of these neurons thereby suppresses norepinephrine release from axon terminals in AHN, probably via an indirect pathway that includes an inhibitory neuromodulator.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for a less rapid increase of heart rate in DS rats remains unclear. Miyajima and Bunag 32,33 suggested that chronic infusion of hypertonic sodium into the third ventricle of Sprague-Dawley rats reduces hypothalamic inhibition of sympathetic vasomotor tone and impairs the baroreflex, which then elevates BP. NaCl uptake by the brain of DS rats appeared to result from increased permeability of the BBB to sodium, whereas renal 22 Na retention resulted from impaired excretion of 22 Na.…”
Section: Discussionmentioning
confidence: 99%